2020
DOI: 10.1038/s41598-020-63485-8
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Bovine and Porcine Milk Exosome Alter miRNAs Profiles in Piglet Serum

Abstract: Breast milk is the most important nutrient source for newborn mammals. Studies have reported that milk contains microRNAs (miRNAs), which are potential regulatory components. Currently, existing functional and nutritional two competing hypotheses in milk field though little date have been provided for nutritional hypothesis. In this study, we used the qRT-PCR method to evaluated whether milk miRNAs can be absorbed by newborn piglets by feeding them porcine or bovine milk. The result showed that miRNA levels (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 80 publications
0
43
0
Order By: Relevance
“…Nonloaded camel milk exosomes contributed to a significant reduction in the progression of breast tumors, as evidenced by increased markers of apoptotic processes as well as oxidative stress reduction and downregulation of several genes associated with inflammatory processes and induction of the immune response [ 91 ]. Because the widespread consumption of milk and dairy products probably contributed to the development of human immune tolerance to milk proteins, milk exosomes can be used as delivery systems for oral drug administration [ 92 ].…”
Section: Milk Exosomes For Drug Delivery In Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Nonloaded camel milk exosomes contributed to a significant reduction in the progression of breast tumors, as evidenced by increased markers of apoptotic processes as well as oxidative stress reduction and downregulation of several genes associated with inflammatory processes and induction of the immune response [ 91 ]. Because the widespread consumption of milk and dairy products probably contributed to the development of human immune tolerance to milk proteins, milk exosomes can be used as delivery systems for oral drug administration [ 92 ].…”
Section: Milk Exosomes For Drug Delivery In Cancer Therapymentioning
confidence: 99%
“…Long noncoding RNA of porcine milk exosomes may interact with miRNA related to cell proliferation, and circular RNA may target miRNA associated with intestinal cells [ 60 ]. A recent paper showed that miRNAs from bovine and porcine milk were adsorbed in piglet intestine and transported to the blood serum with different efficiencies [ 92 ].…”
Section: Biological Activity Of Milk Exosome Nucleic Acids and Delmentioning
confidence: 99%
“…Pasteurized milk transfers bioavailable milk-derived exosomes (MEX) and their gene-regulatory microRNAs (miRs) [ 132 , 133 , 134 , 135 , 136 , 137 ]. Bovine and human MEX and their miRs resist degradative conditions in the gastrointestinal tract, reach the systemic circulation, and distribute in various tissues [ 134 , 138 , 139 , 140 , 141 , 142 , 143 , 144 ]. In fact, increasing evidence presented by studies in humans and animal models supports the view that MEX and their miRs are bioavailable and reach the systemic circulation [ 134 , 136 , 145 , 146 , 147 ], and modify gene expression of the milk recipient [ 132 , 148 , 149 , 150 ].…”
Section: Milk: a Relay For Mtorc1-activation Of The Milk Recipientmentioning
confidence: 99%
“…They suggest that whereas exosomes appear to protect miRNA in the skim milk, this protective effect in the lipid fraction might be due to the exosomes as well, or even because of fat globules or proteins such as Argonaute-2. Lin et al [ 37 ] also proposed that milk-derived miRNA may circulate in plasma joined to proteins, as occurs with some endogenous known miRNA [ 7 , 38 , 39 ]. Another recent study from Smyczynska et al suggests that from all the pasteurization techniques, the High-Pressure Processing method interfere less with miRNA functionality compared to the Holder method [ 40 ].…”
Section: Transport and Absorption Of Breast-milk-derived Mirnasmentioning
confidence: 99%
“…Lin et al [ 37 ] analyzed the miRNA profile in piglet serum after oral administration of bovine and porcine milk and studied the differences in miRNA expression profiles both in in vivo and in vitro experiments. Milk-derived miRNAs were found in the piglets’ serum.…”
Section: Transport and Absorption Of Breast-milk-derived Mirnasmentioning
confidence: 99%